The golden angel Forever angels - Weyn, Suzanne ([Mahwah, N.J.] : Troll, 1996)
Katie agrees to help a mysterious old woman find a buried treasure, but discovers that her true wealth is at home.
8-12.
Keywords: Angels -- Juvenile fiction; Treasure troves -- Fiction